Metaverse-Ready Digital Infrastructure and Logistics Performance in BRICS Economies - Ayşe Güngör (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2025)
This study examines the relationship between metaverse-ready digital infrastructure and logistics performance in BRICS economies. Although the metaverse is increasingly discussed as a transformative digital ecosystem for business, logistics, and supply chain operations, empirical evidence on its infrastructure foundations remains limited, particularly in emerging economies. To address this gap, the study constructs a Metaverse Infrastructure Index (MII) based on internet usage, fixed broadband subscriptions, mobile cellular subscriptions, and ICT service exports. The analysis covers five BRICS economies—Brazil, China, India, Russia, and South Africa—across seven years: 2007, 2010, 2012, 2014, 2016, 2018, and 2023. The final dataset comprises 35 country-year observations. Descriptive statistics, Pearson correlation analysis, multiple linear regression, and panel regression models are employed. Pooled OLS results do not reveal a statistically significant relationship between MII and logistics performance. However, both Fixed Effects and Random Effects models show that MII has a positive and statistically significant effect on logistics performance when country-specific heterogeneity is taken into account. The Hausman test indicates that the Random Effects model may be preferred. The findings suggest that metaverse-ready digital infrastructure can contribute to logistics performance in BRICS economies, but its effect becomes visible only when country-level structural differences are considered.